Efek Penggunaan Maksimum dan Minimum Heat Input di Perbaikan Pipa Menggunakan Metode Weld-Deposition Guna Menghidari Terjadinya Burn-Through dan Hydrogen Cracking - Wira Anom Wibawa; M. N. Ilman (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
Decreasing quality of the pipes damage might influence the business process exploration, production, distribution, and buying and selling of oil and natural gas of a company. One of common method is known cheap and being effectively applied to improve the pipes construction; it is known as weld-deposition. Pipe repair using the weld-deposition method is inseparable from the risk of failure that may occur, namely burn-through and hydrogen cracking. In this study, welding was carried out on API 5L grade B pipes with a diameter of 4 inches and a pipe thickness of 4 mm. Welding is done with a pipe in which there is a flow of water with a flow volume of 5 lpm. The welding parameters used are welding current ranging from 120 A, voltage to 20V, and speed varying from 10 mm/s to 0.5 mm/s which produces heat input ranging from 0.192 kJ/mm to 3.84 kJ/mm. Investigation confirms a mocrostructure and hardness level. This study resulted in recommendations for welding parameters that need to be avoided in order to avoid burn-through and the risk of hydrogen cracking. In this study, there was no burn-through even though the welding was carried out with a high heat input of 3.84 kJ/mm and the minimum heat input was limited to 0.32 kJ/mm so as not to have the potential for hydrogen cracking to occur.Kata kunci: API 5L grade B, weld-deposition, burn-through, hydrogen crack, heat input.